2021
DOI: 10.3390/photonics8120581
|View full text |Cite
|
Sign up to set email alerts
|

A High Precision Fiber Optic Fabry–Perot Pressure Sensor Based on AB Epoxy Adhesive Film

Abstract: This paper proposes a Fabry–Perot pressure sensor based on AB epoxy adhesive with ultra-high sensitivity under low pressure. Fabry–Perot interference, located between single-mode fiber (SMF) and hollow-core fiber (HCF), is an ultra-thin AB epoxy film formed by capillary action. Then the thick HCF was used to fix the HCF and SMF at both ends with AB epoxy adhesive. Experimental results show that when the thickness of AB epoxy film is 8.74 μm, and the cavity length is 30 μm, the sensor has the highest sensitivit… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
7
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 13 publications
(7 citation statements)
references
References 34 publications
(39 reference statements)
0
7
0
Order By: Relevance
“…Being limited by our lab conditions, the temperature responses for different pressures have not been tested. However, it is believed that the temperature sensitivity and the temperature cross-sensitivity for different pressure both increase with the increase of pressure due to the reduction of the F-P cavity length [23].In addition, in our previous work [24], it can be concluded that humidity has a minor influence on the proposed epoxy-based FPI sensor in a specific range of humidity changes. In order to further improve the sensitivity on the basis of the epoxy-filled FPI sensor, an optimized pressure sensor based on the Vernier effect formed by separated cascaded FPIs, is proposed and experimentally demonstrated.…”
Section: B Pressure Sensor With Separated Cascaded Fpi Structures Bas...mentioning
confidence: 84%
“…Being limited by our lab conditions, the temperature responses for different pressures have not been tested. However, it is believed that the temperature sensitivity and the temperature cross-sensitivity for different pressure both increase with the increase of pressure due to the reduction of the F-P cavity length [23].In addition, in our previous work [24], it can be concluded that humidity has a minor influence on the proposed epoxy-based FPI sensor in a specific range of humidity changes. In order to further improve the sensitivity on the basis of the epoxy-filled FPI sensor, an optimized pressure sensor based on the Vernier effect formed by separated cascaded FPIs, is proposed and experimentally demonstrated.…”
Section: B Pressure Sensor With Separated Cascaded Fpi Structures Bas...mentioning
confidence: 84%
“…Optical sensors have been developing rapidly in recent years for their size, cost, networking and multi-parameter sensing but with disadvantages of low mechanical strength [ 51 ]. In Figure 5 a, the reflective index of polymer coating [ 72 , 73 , 74 ] on NCF-AR structure was temperature-sensitive. The seawater salinity is kept at 0‰ and the temperature increases from 15 °C to 35 °C, the transmission signals of the NCF-AR structure have a slope of −4.628 nm/°C in the range of 15 °C to 25 °C.…”
Section: Temperature Sensorsmentioning
confidence: 99%
“…One of the main challenges with fiber optic sensors, especially for strain measurement, is the necessity to guarantee a good adhesion and mechanical match between the sensitive element and the object under test [10]- [13]. The role of epoxy-based adhesives for structural health monitoring is analyzed in [14]- [17], where different adhesives are compared.…”
Section: Introductionmentioning
confidence: 99%